2012
DOI: 10.1080/14680629.2012.749804
|View full text |Cite
|
Sign up to set email alerts
|

Development of an accelerated pavement test reproducing the effect of natural ageing on skid resistance

Abstract: This study deals with the development of a new test method simulating the effect of ageing on skid resistance. This test is applied to bituminous mixes in this study, but can also be applied to concrete. This test relies on two machines, the Wehner–Schulze machine, to measure the friction, and the Weatherometer sunset machine, to simulate weather effects (rain, wind, sunlight, etc.). The relevance of this test is evaluated from comparisons between changes in friction and a chemical function linked to bitumen a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Moreover, ranking between binders, according to the ageing kinetics, is the same for natural and accelerated ageing. This study should provide a better understanding of the influence of ageing on pavement surface properties like skid resistance (Kane, Zhao, Chailleux, Delarrard, & Do, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ranking between binders, according to the ageing kinetics, is the same for natural and accelerated ageing. This study should provide a better understanding of the influence of ageing on pavement surface properties like skid resistance (Kane, Zhao, Chailleux, Delarrard, & Do, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…As the most commonly used materials in the pavement, the common asphalt mixtures' skid resistance development has basically thorough investigated. However, Qian's research on epoxy asphalt mixture shows that with the similar mixture gradation, the skid resistance development trend of epoxy asphalt mixture was the same as the asphalt mixtures but the peak value of epoxy asphalt mixture appeared later and also higher than that of the Kane et al also compared the changes in skid resistance and the carbonyl index, a chemical function linked to asphalt ageing and found that the ageing of the organic phase of the asphalt caused an increase of skid resistance in the first year (Kane, Zhao, Chailleux, Delarrard and Do, 2013). Hadiwardoyo et al investigated the relationship of skid resistance and asphalt penetration index, which shows a fairly strong correlation, the higher the penetration index, the larger skid resistance (Hadiwardoyo, Sinaga and Fikri, 2013).…”
Section: Introductionmentioning
confidence: 94%
“…The repeatability of the test procedure is approximately ±0.026 according to the EN12697-49. Many prediction models for aggregates and asphalt roads are developed based on (Chen and Wang, 2011;Do et al, 2007;Do et al, 2009;Kane et al, 2013;Wang et al, 2013b;Wang et al, 2014a).…”
Section: Wehner/schulze Devicementioning
confidence: 99%